A silk-mineral composite material synthesized by induction using water-soluble silk segments as templates and a preparation method thereof

By using silk fibroin to be soluble in the water chain segment as a template, mineral growth is induced, and the problems of slow mineral growth rate and limited space of silk fibroin membrane templates in the prior art are solved, and a method for efficient preparation of silk fibroin-mineral composites is realized, which is suitable for bone tissue repair.

CN116271250BActive Publication Date: 2025-04-18WUHAN TEXTILE UNIV +1

Patent Information

Application Number
CN202211740460.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-31
Publication Date
2025-04-18
Estimated Expiration
2042-12-31

AI Technical Summary

Technical Problem

In the prior art, it is difficult to induce mineral growth quickly and efficiently at room temperature, and the multi-level growth space of the silk fibroin membrane template is limited, making it difficult to prepare silk fibromine composite materials with specific morphological structures and excellent properties on a large scale.

Method used

The soluble water chain segments in silk fibroprotein are used as templates. The enriched silk fibroprotein is soluble in water chain segments and reacts with calcium ions and hydrogen phosphate ions to induce the orderly growth of minerals at room temperature to form silk fibroprotein-mineral composites.

Benefits of technology

It has achieved efficient regulation of mineral synthesis at low concentrations of silk fibroin, breaking through the growth space limitations of silk fibroin membrane templates, and can quickly prepare silk fibroin-mineral composite materials with specific morphological structures and excellent properties on a large scale, suitable for bone tissue repair materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116271250B_ABST
    Figure CN116271250B_ABST
Patent Text Reader

Abstract

The present invention relates to a silk fibroin mineral composite material synthesized by induction of a silk fibroin water-soluble segment as a template and a preparation method thereof, wherein the silk fibroin mineral composite material is obtained by inducing the orderly growth of calcium ions and hydrogen phosphate ions by the silk fibroin water-soluble segment, and is a bulk mineral formed by the uniform distribution of amorphous calcium phosphate of silk fibroin and amorphous calcium phosphate growing along the c-axis, or rod-shaped calcium hydrogen phosphate crystals juxtaposed and aggregated, and the surface of the bulk mineral is coated with silk fibroin. The silk fibroin mineral composite material provided by the present invention has a unique oriented structure, has a large potential application value in the preparation of bone tissue repair materials, can be induced by the induction of the silk fibroin water-soluble segment, add a phosphorus source and a calcium source, induce the directional growth of minerals at the wound, and realize the rapid regeneration and repair of bone tissue.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of prosthetic materials or prosthetic covering materials, and particularly relates to a silk fibroin-mineral composite material synthesized by induction using water-soluble silk fibroin segments as templates and a preparation method thereof. Background Art

[0002] Silk fibroin in nature has excellent mechanical properties, biocompatibility, and controllable assembly structure. Its potential application in biomineralization and biomimetic material preparation has attracted the interest of scientists. The unique precision multi-level structure of silk fibroin can be used as a unique biological template. In addition, traditional hard templates need to be pretreated to obtain functional groups that can be controlled for mineralization on the surface, while silk fibroin itself contains a rich variety of amino acids and functional groups and can be used directly as a template.

[0003] Silk fibroin can be used as a biological template for the synthesis and preparation of biomimetic materials, and its structure and properties will have a great impact on the prepared materials. Silk fibroin is an aggregate of three polypeptide chains, including a relatively large molecular weight peptide heavy chain (H chain, 390kDa), a relatively small molecular weight light chain (L chain, 25kDa) and a p25 glycoprotein segment (p25, 30kDa), in which the H chain and the L chain are connected by a pair of disulfide bonds, and p25 is connected to these two segments through hydrophobic interaction. The H chain, as the core part of the silk fibroin body, is a repeating region of the GAGAGS sequence. This region is easier to self-aggregate to form a hydrophobic β-pleated sheet due to its regular skeleton structure and small side chains. Unlike the H chain, the L chain and the p25 chain contain a large number of hydrophilic amino acids, such as arginine, tyrosine and phenylalanine.

[0004] In the past, many studies have directly used silk fibroin to regulate the orderly growth of minerals or metal oxides. Due to the template properties of silk fibroin, it can induce minerals and metal oxides to grow in a directional manner along the c-axis. However, it usually takes a long time to achieve the ideal regulation state. To speed up the regulation rate, it is usually necessary to use a higher concentration of silk fibroin solution or apply high heat or high pressure conditions externally.

[0005] The present application extracts water-soluble segments from silk fibroin as templates, induces the orderly growth of minerals at room temperature, synthesizes silk fibroin-mineral composite materials, and achieves the purpose of efficiently regulating mineral synthesis with low-concentration protein. It also breaks through the problem of limited space for multi-level mineral growth on silk fibroin membranes in the process of inducing mineral growth using silk fibroin membranes as templates in the past, improves the volume of solutions containing water-soluble segments, and can efficiently prepare a large number of silk fibroin-mineral composite materials. By cleverly combining organic polymers with inorganic materials, composite materials with specific morphological structures and excellent performance can be obtained. Summary of the invention

[0006] The technical problem to be solved by the present invention is to address the above-mentioned deficiencies in the prior art and to provide a silk fibroin-mineral composite material induced by synthesis using water-soluble silk segments as templates, and a preparation method and application thereof. The water-soluble silk fibroin segments enriched in the silk fibroin protein are used as templates to induce mineral growth, and the regulation efficiency is much higher than that of a pure silk fibroin protein solution. A low-concentration and high-efficiency regulation method can be achieved to obtain a silk fibroin-mineral composite material with a specific morphology and excellent performance.

[0007] In order to solve the above technical problems, the technical solution provided by the present invention is:

[0008] Provided is a silk fibroin-mineral composite material synthesized by induction using water-soluble silk segments as templates. The silk fibroin-mineral composite material is obtained by inducing the orderly growth of calcium ions and hydrogen phosphate ions by the water-soluble silk segments, and is a bulk mineral formed by a spindle-like structure of uniformly distributed silk fibroin and amorphous calcium phosphate growing along the c-axis, or by parallel aggregation and growth of rod-shaped calcium hydrogen phosphate crystals, and the surface of the bulk mineral is coated with silk fibroin.

[0009] The present invention also includes a method for preparing the above-mentioned silk fibroin-mineral composite material using the water-soluble silk fibroin segment as a template for induction synthesis, and the specific steps are as follows:

[0010] 2) Preparation of water-soluble silk fibroin segment solution: soak degummed silk in lithium bromide solution and heat to dissolve to obtain a crude solution, place the crude solution in a dialysis bag, dialyze in deionized water to remove salt ions, centrifuge to obtain a supernatant to obtain a regenerated silk fibroin solution, spread the obtained regenerated silk fibroin solution in a culture dish and place it in a clean bench to dry to obtain a silk fibroin membrane, cut the obtained silk fibroin membrane into pieces and soak it in deionized water, place it on a shaker for 60 to 90 minutes, centrifuge to obtain a supernatant and dilute it to obtain a WSF solution (water-soluble silk fibroin segment solution);

[0011] 3) Preparation of silk-mineral composite material induced by the synthesis of water-soluble silk segments as templates: CaCl2 was dissolved in the WSF solution obtained in step 1) to obtain a WSF solution containing CaCl2, and a mixed solution of KH2PO4 and Na2HPO4 (buffer) was placed in an ice-water bath and mixed for 30 min, and the pH value of the solution was stabilized at 6.

[0012] ±0.5, and then the WSF solution containing CaCl2 is added into a mixed solution of KH2PO4 and Na2HPO4 to carry out a mineralization reaction. After the reaction is completed, the solid product is collected by centrifugation to obtain a silk-mineral composite material induced and synthesized using the water-soluble silk segment as a template.

[0013] According to the above scheme, the lithium bromide solution in step 1) is obtained by dissolving lithium bromide in water, and the concentration is 9.3M (mol / L); the mass volume ratio of the degummed silk to the lithium bromide solution is 0.15-0.25g / mL.

[0014] According to the above scheme, the process conditions of step 1) soaking the degummed silk in a lithium bromide solution and heating to dissolve are: stirring at 60° C. at a rate of 200 to 400 rpm for 2 to 4 hours.

[0015] According to the above scheme, the concentration of the regenerated silk fibroin solution in step 1) is 6-7 wt%.

[0016] According to the above scheme, in step 1), the obtained silk fibroin membrane is cut into pieces and then immersed in deionized water, and the mass volume ratio of the silk fibroin membrane to the deionized water is 0.05-0.15 g / mL.

[0017] According to the above scheme, the concentration of water-soluble segments of silk fibroin in the WSF solution in step 1) is 0.05-0.25 wt %.

[0018] According to the above scheme, the concentration of CaCl2 in the WSF solution containing CaCl2 dissolved in step 2) is 5-10 mM (mmol / L).

[0019] According to the above scheme, the concentration of hydrogen phosphate in the mixed solution of KH2PO4 and Na2HPO4 in step 2) is 5-10 mM, wherein the mass ratio of KH2PO4 to Na2HPO4 is 1:3.65.

[0020] According to the above scheme, the molar ratio of calcium in the WSF solution containing CaCl2 dissolved therein in step 2) to phosphorus in the mixed solution of KH2PO4 and Na2HPO4 is 1.67:1, and the Ca 2+ The concentration is 5-10mM.

[0021] According to the above scheme, the mineralization reaction conditions in step 2) are: reacting at room temperature (20-30° C.) for 0.5-24 hours.

[0022] The present invention also includes the use of the silk fibroin-mineral composite material synthesized by induction using the water-soluble silk fibroin chain segment as a template in the preparation of bone tissue repair materials.

[0023] Silk fibroin has a special composition structure and template characteristics. Due to the difference in amino acid composition and charge in different segments of silk fibroin, it has a certain negative impact on the growth of minerals. The present invention separates and extracts the water-soluble segments in silk fibroin. This segment contains more positively charged amino acids, which reduces the electrostatic repulsion between negatively charged amino acids, making it easier to polymerize and cross-link to form silk fibroin segment aggregates. In the silk fibroin segment aggregates, negatively charged groups tend to aggregate on the surface, making Ca 2+ It is easier to combine with silk fibroin. During the mineralization process, the cross-linking of silk fibroin and the interaction with Ca 2+ The combination of the mineral and the silk protein clusters occurs alternately, so that the mineral and the silk protein clusters are combined and grown, and finally a coating structure is formed. The present invention can quickly prepare oriented calcium hydrogen phosphate minerals on a large scale.

[0024] The beneficial effects of the present invention are as follows: 1. The silk fibroin-mineral composite material provided by the present invention has a unique oriented structure and has great potential application value in the preparation of bone tissue repair materials. Through the induction of the water-soluble chain segments of silk fibroin, phosphorus sources and calcium sources are added to induce the directional growth of minerals at the wound, thereby achieving rapid regeneration and repair of bone tissue. 2. The preparation method of the present invention has mild reaction conditions, good repeatability, and a simple preparation process. It can be prepared quickly and in large quantities through the induction of WSF, and is easy to carry out large-scale production and preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a comparison diagram of the SF solution and the WSF solution prepared in Example 1 of the present invention;

[0026] Figure 2 XRD photos of the SF solution and WSF solution prepared in Example 1;

[0027] Figure 3 FTIR photos of the SF solution and WSF solution prepared in Example 1;

[0028] Figure 4 CD spectra of the SF solution and WSF solution prepared in Example 1;

[0029] Figure 5 The particle size distribution diagram of the SF solution and the WSF solution prepared in Example 1;

[0030] Figure 6 zeta potential diagrams of the SF solution and the WSF solution prepared in Example 1;

[0031] Figure 7 This is a comparison chart of the surface tension of the SF solution and the WSF solution prepared in Example 1;

[0032] Figure 8 The contact angle photos of the SF solution and the WSF solution prepared in Example 1;

[0033] Fig. 9 The morphology, XRD and FTIR comparison diagram of the mineral products of the blank control group of Example 1 from the beginning of the reaction to 24 hours of reaction;

[0034] Fig.10 The SEM images of the products obtained by inducing mineralization of the SF solution and the WSF solution prepared in Example 1 for 0.5 h, 2 h and 24 h;

[0035] Fig.11 XRD patterns of the minerals obtained by inducing mineralization for 0.5 h, 2 h and 24 h with the SF solution and WSF solution prepared in Example 1;

[0036] Fig.12 FTIR spectra of the minerals obtained by inducing mineralization of SF solution and WSF solution prepared in Example 1 for 0.5h, 2h and 24h;

[0037] Fig.13 (a) TEM photo of the mineral obtained by mineralization induced by the WSF solution prepared in Example 1 for 0.5 h; (b) SAED; (c, d) HRTEM; (e) TEM bright field image; (f) TEM dark field image; (g) EDS-mapping photo;

[0038] Fig.14 The SF solution (a) and WSF solution (b) prepared in Example 2 with different concentrations were mixed with Ca 2+ After the photo and further addition of HPO4 2- Photos of the mineral precipitation state obtained after the solution was mineralized for 0.5h (c, d);

[0039] Fig.15 The SEM images of the mineral precipitates obtained by mineralizing the 0.25wt% and 0.10wt% SF solutions and WSF solutions prepared in Example 2 for 0.5h and 2h;

[0040] Fig.16 XRD patterns of minerals obtained from the 0.25wt% and 0.10wt% SF solutions and WSF solutions prepared in Example 2 after mineralization for 0.5h and 2h;

[0041] Fig.17 FTIR spectra of the minerals obtained from the mineralization of 0.5h and 2h of SF solution and WSF solution with concentrations of 0.25wt% and 0.10wt% prepared in Example 2;

[0042] Fig.18 The SEM, XRD and FTIR images of the products obtained from the blank group of Example 3 at different reaction times;

[0043] Fig.19 The SEM images of the mineral precipitates obtained by mineralizing the SF solution and WSF solution with concentrations of 0.25wt% and 0.10wt% prepared in Example 3 for 0.5h and 2h;

[0044] Fig. 20 XRD patterns of minerals obtained by mineralization of 0.5h and 2h of SF solution and WSF solution with concentrations of 0.25wt%, 0.10wt% and 0.05wt% prepared in Example 3;

[0045] Fig.21 FTIR spectra of the minerals obtained from the mineralization of 0.25wt%, 0.10wt% and 0.05wt% SF solutions and WSF solutions prepared in Example 3 after 0.5h and 2h of mineralization. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.

[0047] The degummed silk used in the embodiments of the present invention was purchased from Suzhou Simet Biotechnology Co., Ltd.

[0048] Example 1

[0049] A silk-mineral composite material synthesized by inducing the synthesis of silk fibroin water-soluble segments as templates, the specific preparation steps are as follows:

[0050] The steps are as follows:

[0051] 1) Preparation of silk fibroin solution (SF solution): 10 g of degummed silk was added to 40 mL of 9.3 M lithium bromide solution, and the lithium bromide solution was placed in a 60° C. water bath for heating and stirred at 400 rpm for 2 h to destroy the structure of the silk fibroin and dissolve the silk fibroin. The reaction solution was placed in a 14000 kd dialysis bag and dialyzed in an ice water bath for 72 h to remove excess salt ions. The dialyzed solution was centrifuged to remove the precipitate to obtain a 6 wt % silk fibroin solution (SF solution), which was stored in a 4° C. refrigerator;

[0052] 2) Preparation of water-soluble silk fibroin segment solution (WSF solution): Spread the silk fibroin solution obtained above in a 90 mm × 15 mm round culture dish, then place the culture dish in a clean bench, maintain constant temperature (28° C.) and relative humidity (40%) overnight to obtain a transparent silk fibroin film, cut the silk fibroin film into 20 mm × 5 mm strips with scissors, then soak 1.0 g of the silk fibroin film in 20 mL of deionized water, and place it on a shaker in a 37° C. water bath for 90 min to obtain the soluble segments (WSF) in the silk fibroin, centrifuge the obtained solution, take the supernatant, which is the water-soluble silk fibroin segment solution (WSF solution, concentration is about 2 wt%), and store it in a 4° C. refrigerator;

[0053] 3) 0.0505 g of CaCl2 powder was dissolved in 20 mL of SF solution and WSF solution with a concentration of 0.05 wt% after dilution, respectively, to obtain SF solution and WSF solution (CaCl2 concentration was 22.75 mM) containing CaCl2, and then a plurality of KH2PO4 and Na2HPO4 mixed solutions were prepared, wherein each mixed solution was prepared by dissolving 0.01375 g of KH2PO4 and 0.05 g of Na2HPO4 in 70 mL of deionized water, so that the concentration of hydrogen phosphate was 6.475 mM, and the pH value of the solution was stabilized at 6±0.5, the prepared KH2PO4 and Na2HPO4 mixed solution was placed in an ice water bath and stirred for 30 min to mix them evenly, and the above-prepared SF solution and WSF solution (20 mL) containing CaCl2 were added to a 70 mL volume of KH2PO4 and Na2HPO4 mixed solution for mineralization reaction, at which time the Ca in the reaction system was 1.5 wt% and 1.5 wt% respectively. 2+ The initial reaction concentration was 5 mM. Samples were taken at different mineralization time points (0.5 h, 2 h and 24 h). The samples were separated by centrifugation at 9000 r / min for 15 min. The precipitate was resuspended and washed with deionized water and then centrifuged again to obtain the mineralization product. The prepared samples were freeze-dried and stored in a vacuum drying oven.

[0054] like Figure 1 Shown is a comparison diagram of different silk fibroin segments prepared in this example, Figure 1 a and b are SEM images of the dried products of the SF solution and WSF solution prepared in this example after gelation, respectively. The SF solution and WSF solution were ultrasonically treated for 10 min and then placed in a 36°C incubator for 30 min. Figure 1d, where the left is SF solution and the right is WSF solution. It can be seen that the WSF solution can self-assemble and cross-link to form a gel faster. The two protein gels were freeze-dried and then subjected to SEM testing. The SEM results showed that the morphologies of silk protein and its separated segments were different. The protein distribution in the SF gel was more uniform, and the WSF gel had a faster agglomeration rate, so there were many silk nanoparticles with a size of about 500 nm inside. Figure 1 c is a photograph of the SF solution (left) and the WSF solution (right) prepared in this example. It can be seen that the SF solution is a transparent solution and the WSF solution is a translucent white solution.

[0055] The difference between SF solution and WSF solution can also be shown by various tests such as XRD, FTIR, circular dichroism (CD spectrum), particle size distribution, zeta potential, surface tension and contact angle ( Figure 2-8 ,).

[0056] The molecular conformation and condensed structure of SF and WSF were studied. XRD results ( Figure 2 ) showed that the two proteins had broad diffraction peaks at 13.0°, indicating that they were amorphous aggregated Silk I structures, while WSF also showed broad diffraction peaks of Silk I at 20.1° and 31.0°, respectively, and also had a broad diffraction peak corresponding to the β-folded structure at 40°. The FTIR test results of the two proteins ( Figure 3 ) did not show significant differences, both at 1649cm -1 (amide I, random curl), 1519 cm -1 (amide II, β-fold) and 1240 cm -1 (amideⅢ, β-folding) has a more obvious absorption peak. After normalization, it is found that the absorption peak at 1519cm -1 There is a stronger absorption peak in the amideⅡ domain of the two proteins, which means that it contains more β-folded structures. In order to test the differences in molecular conformation and structure of the two proteins in liquid state, circular dichroism spectroscopy was used to detect the two protein solutions. The CD spectra of the two protein solutions showed a large difference ( Figure 4 ), both proteins have positive Coton peaks at 192nm and negative Coton peaks at 216nm, which respectively represent the β-fold and β-turn structures of silk fibroin. However, the contents of these two structures in the two proteins are quite different. The contents of β-fold and β-turn structures are the highest in WSF, while the contents in SF are relatively low. The above results all indicate that a more stable structure exists in WSF solution.

[0057] Figure 5The particle size distribution diagram shows that there is a huge difference in the particle size of the two proteins. The average particle size of the protein particles in the WSF solution is 69.59nm, while the protein particle size in the SF solution is 5.549nm. It can be found that the protein aggregates in the WSF solution to form a larger particle structure. Zeta potential results ( Figure 6 ) showed that both protein solutions were negatively charged, with WSF having a slightly stronger charge of -7.98 mV and SF having a charge of -5.96 mV. Figure 7 ) found that under the condition of equal concentration, the surface tension of WSF is higher than that of SF. This result shows that the polarity of WSF solution is stronger than that of SF solution. The contact angle test results of these two solutions on the surface of PDMD film ( Figure 8 ) also showed the same trend, that is, WSF had a larger contact angle, indicating a stronger hydrophilicity, and also exhibited a stronger polarity.

[0058] In order to explain the reasons for these differences, the present invention tested the types and contents of amino acids in the water-soluble segments of silk fibroin in SF solution and WSF solution. The test results are shown in Table 1.

[0059] Table 1

[0060]

[0061] The test results show that the water-soluble segments of silk fibroin carry more positively charged amino acids (lysine, arginine, histidine, etc.). Therefore, the positively charged amino acids contained in the water-soluble segment solution slow down the electrostatic repulsion between the negatively charged amino acids, allowing the amino acid macromolecular segments to stretch and interact and assemble to form aggregates. The weak physical interaction between the aggregates causes the amino acids in the water-soluble segments to aggregate rapidly, eventually forming a large and stable particle structure. The more stretched molecular chain structure in the water-soluble segments gives it greater surface tension. During the process of amino acid molecular chain assembly and arrangement, the negatively charged segments tend to aggregate and assemble on the particle surface, making the water-soluble segments show stronger negative charge.

[0062] The SF solution and WSF solution (20 mL) containing CaCl2 in this embodiment were added to 70 mL of a mixed solution of KH2PO4 and Na2HPO4 for mineralization reaction, and the products were subjected to SEM and XRD tests and compared with a blank control group, which was obtained by dissolving 0.0505 g of CaCl2 powder in 20 mL of deionized water, adding 70 mL of a mixed solution of KH2PO4 and Na2HPO4 for mineralization reaction, and then separating and precipitating. Fig. 9The figure shows the morphology, XRD and FTIR comparison of the mineralization products of the blank control group from the beginning of the reaction to 24 hours of reaction. It can be seen that in the blank control group without protein regulation of natural growth, the minerals obtained in the early stage of mineralization are amorphous calcium phosphate particles with spherical structures. As the mineralization reaction proceeds, plate-like calcium hydrogen phosphate minerals will be formed in the later stage of mineralization. Fig. 9 The XRD results of b show that there is a strong crystalline peak at 24h of mineralization, and the amorphous peak package is very small, proving that the mineral crystallization is relatively complete at this time. Fig.10 The SEM images of the products obtained under different mineralization times of SF solution and WSF solution, among which the mineral particles grown along the c-axis in the early stage of WSF-regulated mineral growth ( Fig.10 b1, b2), and in the late stage of mineralization, rod-shaped calcium hydrogen phosphate can be observed to grow in a directional manner to form a regular block mineral, and the mineral surface is coated with silk fibroin ( Fig.10 b3, b4).

[0063] In the early stage of mineralization in SF solution, amorphous calcium phosphate particles are formed, and spindle-shaped minerals are also generated in the middle stage of mineralization. In the late stage of mineralization, the induction and inhibition of SF solution on minerals weakens, causing the minerals to grow into disordered block minerals. However, there are more granular amorphous calcium phosphate particles around the minerals, indicating that SF still has a certain inhibitory effect. Fig.11 (a) and (b) are the XRD patterns of the products obtained at different mineralization times in SF solution and WSF solution, respectively. Fig.12 (a) and (b) are FTIR images of the products obtained at different mineralization times in SF solution and WSF solution, respectively. XRD and FTIR results show that the minerals in the solution are all calcium phosphate (ACP) in the early stage of mineralization (0.5-2h), but the final products obtained after 24h of mineralization are all calcium hydrogen phosphate (DCPD). Compared with the blank control group, SF and WSF solutions have an inhibitory effect on the growth of minerals in the early stage of mineralization. The minerals in the blank control group have all grown into massive calcium hydrogen phosphate at 2h, and the crystallization is relatively complete after 24h of mineralization. In the protein-regulated solution, the minerals after 2h of mineralization still exist in the state of amorphous calcium phosphate ACP, a mineral precursor. After 24h of mineralization, XRD shows that although the minerals obtained by the two protein-regulated methods are all crystallized, the amorphous broad diffraction peak still exists. This result also shows the inhibitory effect of silk fibroin and its water-soluble segments on mineral growth.

[0064] The minerals obtained by WSF control were further analyzed by transmission. The results showed that particle clusters and spindle-like minerals were formed at 0.5h of mineralization. The mineral size was about 40-100nm ( Fig.13 a, e, f). Selected area electron diffraction ( Fig.13b) The sample is still in an amorphous state. Using high resolution to explore the cluster particles, the cluster particles have hollow structures inside and mineral epitaxial growth on the surface of the cluster particles ( Fig.13 c) Organic matter is coated on the outside of the grown minerals ( Fig.13 d). EDS-mapping( Fig.13 g) The results show that although the content of silk fibroin in the spindle-like mineral is low, it is evenly distributed in the mineral structure (C, S, N represent the distribution of silk fibroin, Ca, P, O represent the distribution of minerals). In the WSF solution, due to the presence of more positively charged amino acids, there is a more obvious aggregation phenomenon. Since the negatively charged segments tend to be arranged on the surface during the assembly and arrangement of amino acids, WSF clusters are very easy to assemble with Ca 2+ Due to Ca 2+ Aggregate on the surface of silk clusters, making the surface Ca 2+ The concentration reaches local supersaturation, causing the unstable crystal phase to form rapidly on the surface of the cluster and grow epitaxially. During the mineral growth process, the silk protein of the nanocluster forms a coating and template effect on the mineral, and the outside of the cluster reacts with the inorganic mineral to form a shell and extend outward to mineralize ( Fig.13 c). In addition, since more β-folded structures are formed inside the WSF clusters, this structure is the main reason why silk fibroin, as a macromolecular template, has a regulatory effect on mineral morphology.

[0065] Example 2

[0066] A silk-mineral composite material synthesized by induction using water-soluble silk segments as templates, wherein the specific preparation steps are as follows:

[0067] 1) Preparation of silk fibroin solution (SF solution): 10 g of degummed silk was added to 40 mL of 9.3 M lithium bromide solution, and the lithium bromide solution was placed in a 60° C. water bath for heating, and stirred at 400 rpm for 2 h to dissolve the silk fibroin. The reaction solution was placed in a 14000 kd dialysis bag and dialyzed in an ice water bath for 72 h to remove excess salt ions. The dialyzed solution was centrifuged to remove the precipitate to obtain a 6 wt % silk fibroin solution, which was stored in a 4° C. refrigerator;

[0068] 2) Spread the silk fibroin solution obtained above in a 90 mm × 15 mm circular culture dish, then place the culture dish in a clean bench, maintain constant temperature (28 ° C) and humidity (40%) overnight to obtain a transparent silk fibroin film, cut the silk fibroin film into 20 × 5 mm strips with scissors, soak 1.0 g of the protein film in 20 mL of deionized water, and shake it on a shaker in a 37 ° C water bath for 90 min to obtain the soluble segment (WSF) of the silk fibroin, centrifuge the obtained solution, take the supernatant, which is the water-soluble segment solution of silk fibroin (WSF solution, the solution concentration is about 2wt%), and store it in a 4 ° C refrigerator;

[0069] 3) 0.0505 g of CaCl2 was dissolved in 20 mL of diluted SF solution and WSF solution with concentrations of 0.25 wt%, 0.10 wt% and 0.05 wt% respectively to obtain SF solution and WSF solution with CaCl2 concentration of 22.75 mM. Then, multiple portions of KH2PO4 and Na2HPO4 mixed solution were prepared, wherein each portion of KH2PO4 was 0.01375 g and each portion of Na2HPO4 was 0.05 g dissolved in 70 mL of deionized water to make the phosphate concentration 6.475 mM and the pH value of the solution stabilized at 6 ± 0.5. The prepared KH2PO4 and Na2HPO4 mixed solution was placed in an ice water bath and stirred for 30 min to mix them evenly. SF solution and WSF solution (20 mL) with CaCl2 dissolved in different concentrations were added to 70 mL of KH2PO4 and Na2HPO4 mixed solution for mineralization reaction. At this time, Ca in the reaction system 2+ The initial reaction concentration was 5 mM. Samples were taken at different mineralization time points of 0.5 h and 2 h. The samples were separated by centrifugation at 9000 r / min for 15 min. The precipitate was resuspended and washed with deionized water and then centrifuged again to obtain the mineralization product. The prepared samples were freeze-dried and stored in a vacuum drying oven.

[0070] In this example, the effect of different protein concentrations on the nucleation and growth of calcium phosphate minerals was explored. Protein concentrations of 0.25wt%, 0.10wt% and 0.05wt% were selected to prepare mineralization solutions, CaCl2 was added, and the test tube was gently shaken on a shaker to dissolve the CaCl2. After 0.5h, the states of the different protein solutions were observed and compared with SF solutions of the same concentration. Fig.14 It is shown that SF 2+ After that, it was still a clear solution ( Fig.14 a), WSF solution is in Ca 2+ After adding Fig.14 b), the protein solution with the highest concentration of 0.25wt% changes the most drastically, and the color of the solution changes in a gradient as the protein concentration decreases.2+ There is a strong interaction between silk fibroin and metal ions. Under the action of polar amino acids, silk fibroin can form complexes with metal ions. Through the study of the two proteins, it is known that there are more cluster structures with negatively charged amino acids on the surface in high-concentration WSF solutions, which are more likely to interact with Ca 2+ To combine.

[0071] Then, the Ca dissolved 2+ Two protein solutions of different concentrations were added with HPO4 2- The precipitation state was observed after 0.5h of reaction. The results showed that ( Fig.14 c) In the 0.25wt% SF solution, no minerals have been precipitated. As the concentration decreases, more precipitates are gradually generated. Under the control of WSF, the formation of precipitates has been observed in the 0.25wt% solution ( Fig.14 d), this is because there are more self-assembled nanoclusters in WSF, forming larger mineral particles that are easy to precipitate. However, in WSF solution, the minerals in high protein concentration solution precipitate slowly, while the minerals in low protein concentration solution precipitate quickly. This phenomenon proves that high concentration of silk fibroin has an inhibitory effect on the nucleation and crystallization of minerals.

[0072] The morphology and phase of the minerals were detected, showing that under the control of two silk fibroin solutions with different concentrations, the early generated minerals (mineralization 0.5h) were all spherical ACP particles ( Fig.15 a1, b1, a3, b3), proving that high concentration protein solution has an inhibitory effect on the nucleation and crystallization of minerals. This result is consistent with Fig.14 The phenomenon in the experiment is consistent. Since high-concentration proteins have more macromolecular segments, the increased macromolecular segments in the solution will slow down the movement and collision of calcium / phosphorus ions, thereby reducing the crystallization rate of DCPD. Unlike the minerals obtained by regulating 0.05wt% WSF for 0.5h, the ACP obtained by regulating high-concentration WSF at this time point is still spherical. It can be seen that there are a large number of negatively charged protein clusters in high-concentration WSF and free Ca in the solution. 2+ Combined with each other, local supersaturation is formed, thus promoting the mineralization reaction. After the formation of ACP / silk fibroin hybrid particles, due to the Ca 2+ The negatively charged protein clusters in the solution are attracted to aggregate and the mineral particles are coated. The formation of the coating structure reduces the collision of calcium / phosphorus ions, thereby inhibiting further crystallization. Therefore, under the regulation of WSF solution, the energy required for the conversion of ACP to DCPD is higher, and the stability of the mineral in the protein solution is also enhanced, and it is still amorphous ACP ( Fig.15 b2) The protein segments in SF will not assemble into larger aggregates, but will still interact with Ca 2+The acidic amino acids in silk protein regulate the growth of minerals, thus inhibiting the growth of minerals. In the late stage of mineralization, the inhibitory effect of protein on minerals weakens. This is because the protein grows in combination with crystals, regulating the morphology of minerals and orienting their growth, forming a spindle-shaped particle structure ( Fig.15 a2, a4, b4).

[0073] Fig.16 The XRD patterns of the minerals obtained after mineralization of 0.5h and 2h by 0.25wt% and 0.10wt% silk fibroin solutions and their water-soluble segment solutions in different concentration systems. The results show that the minerals obtained after mineralization of 2h by pure silk fibroin solutions and their water-soluble segment solutions in different concentration systems are basically amorphous ACP, and only a small amount of crystal formation is found in the SF regulation system. The protein coating structure in WSF will inhibit crystal growth. Acidic proteins also exist in SF, so high concentrations of SF proteins also have an inhibitory effect on mineral growth. The XRD patterns of the mineral growth regulated by SF for 0.5h and 2h show the presence of a broad diffraction peak of ACP ( Fig.16 a). In the XRD spectrum of the mineral growth regulated by 0.25wt% WSF for 0.5h, there is a broad peak of SilkⅠ at 20° ( Fig.16 b), proving that there are more WSF in the formed mineral structure. FTIR results of the two proteins regulating the minerals ( Fig.17 a, b) are both 1500cm -1 and 1600cm -1 The absorption peak of silk fibroin is at 1000 cm -1 and 550cm -1 The absorption peak of ACP is at the position. After normalizing the FTIR results and comparing them, it can be found that the mineral regulated by the high concentration protein solution in the early stage of mineralization has a stronger silk protein absorption peak, and after the protein concentration is reduced, the absorption peak of ACP is significantly enhanced. In the sample of mineralization for 2h, due to the Ca 2+ At the same concentration, the nucleation and crystallization of minerals are completely affected by silk fibroin. In the SF mineralization system, the change of silk fibroin concentration only shows a difference in the absorption peak of the protein ( Fig.17 a). In the WSF regulation system, the high-concentration protein system has a stronger protein absorption peak, while the low-concentration WSF system has a stronger ACP absorption peak ( Fig.17 b) This phenomenon indicates that the concentration difference of silk fibroin has the most obvious effect on the regulation of mineral formation in the WSF system.

[0074] Example 3

[0075] A silk-mineral composite material synthesized by induction using water-soluble silk segments as templates, wherein the specific preparation steps are as follows:

[0076] 1) Preparation of silk fibroin solution (SF solution): 10 g of degummed silk was added to 40 mL of 9.3 M lithium bromide solution, and the lithium bromide solution was placed in a 60° C. water bath for heating, and stirred at 400 rpm for 2 h to destroy the structure of the silk fibroin and dissolve the silk fibroin. A 14000 kd dialysis bag was used to place the reaction solution in an ice water bath for 72 h to remove excess salt ions. The dialyzed solution was centrifuged to remove the precipitate to obtain a 6 wt % silk fibroin solution, which was stored in a 4° C. refrigerator;

[0077] 2) Spread the silk fibroin solution obtained above in a 90mm×15mm round culture dish, then place the culture dish in a clean bench, maintain constant temperature (28°C) and humidity (40%) overnight to obtain a transparent silk fibroin film, cut the silk fibroin film into 20mm×5mm strips with scissors, soak 1.0g of the protein film in 20mL of deionized water, and shake it on a shaker in a 37°C water bath for 90min to obtain the soluble segment (WSF) in the silk fibroin. Centrifuge the obtained solution, take the supernatant, which is the water-soluble segment solution of silk fibroin (WSF solution, solution concentration is about 2wt%), and store it in a 4°C refrigerator;

[0078] 3) 0.1010 g of CaCl2 powder was dissolved in 20 mL of diluted 0.25 wt%, 0.01 wt% and 0.05 wt% SF solution and WSF solution, respectively, to obtain SF solution and WSF solution with CaCl2 concentration of 45.50 mM. Then, multiple portions of KH2PO4 and Na2HPO4 mixed solution were prepared, wherein each portion of KH2PO4 was 0.0275 g and each portion of Na2HPO4 was 0.1 g dissolved in 70 mL of deionized water, so that the phosphate concentration was 12.95 mM, and the pH value of the solution was stabilized at 6 ± 0.5. The prepared KH2PO4 and Na2HPO4 mixed solution was placed in an ice water bath and stirred for 30 min. 20 mL of SF solution and WSF solution with different concentrations of CaCl2 were added to 70 mL of KH2PO4 and Na2HPO4 mixed solution for mineralization reaction. At this time, Ca in the reaction system 2+ The initial reaction concentration was 10 mM. Samples were taken at different mineralization time points of 0.5 h and 2 h. The samples were separated by centrifugation at 9000 r / min for 15 min. The precipitate was resuspended and washed with deionized water and then centrifuged again to obtain the mineralization product. The prepared samples were freeze-dried and stored in a vacuum drying oven.

[0079] In this example, the concentration of the mineralization system was increased to 10 mM. The blank group mineral was obtained by dissolving 0.1010 g of CaCl2 powder in 20 mL of deionized water, adding 70 mL of a mixture of KH2PO4 and Na2HPO4, and then separating and precipitating. The SEM test results of the blank group mineral showed that the 10 mM mineralization system still formed spherical ACP particles in the initial state ( Fig.18 a), after 0.5h of reaction, flake DCPD was formed ( Fig.18 b). XRD and FTIR test of the blank group mineral products obtained at different reaction times ( Fig.18 c, d) show that although more plate-like crystals have been formed at 0.5h, amorphous particles still exist, and ACP is basically converted into DCPD at 2h of mineralization. It can be seen that increasing the concentration of the mineralization solution significantly accelerates the crystallization rate. This is because the driving force for crystallization in the solution is enhanced, breaking the metastable balance, causing the amorphous calcium phosphate to transform into a more stable crystal structure.

[0080] The use of different silk fibroin in the high concentration mineralization system has a regulatory effect on mineral formation. 2+ The initial reaction concentration was increased to 10 mM, and two different concentrations of SF and WSF, 0.25 wt% and 0.05 wt%, were used to regulate mineral growth. Fig.19 It shows that high concentration of silk fibroin (0.25wt% SF and WSF) has an inhibitory effect on mineral growth and crystallization. After 2h of mineralization, there are still many spherical particles ( Fig.19 a2, b2). However, unlike the results of mineralization of 5 mM high concentration silk fibroin for 2 h in Example 1, the morphology of amorphous mineral particles ACP did not show regulation regardless of high or low protein concentrations during the reaction, in the 10 mM SF-containing mineralization solution (0.25 wt% and 0.05 wt% reaction for 0.5-2 h), and remained spherical particles ( Fig.19 a1-a4). When the protein concentration decreases, the degree of mineral crystallization increases and the crystallization rate accelerates, but the formation of spindle-shaped particles is only found in the product of 0.05wt% WSF mineralization for 2h ( Fig.19 b4) In the previous two examples, the difference between pure silk fibroin and its water-soluble segments in regulating mineral formation was described. SF regulates minerals by interacting with acidic amino acids dispersed in the solution and crystals. Too fast a crystallization rate will reduce the interaction between amino acids and crystal surfaces, and the regulation of mineral morphology will be weakened. In WSF, Ca 2+Combine with protein clusters in the solution to control the formation of crystals at the mineralization site. Since the clusters contain a large number of β-folded structures, the mineral morphology can still be regulated despite the accelerated crystallization rate. When the protein solution concentration is high, the formed coating structure will inhibit crystal growth. When the protein concentration is reduced, the crystallization rate is accelerated, but because the mineral grows after combining with the protein clusters, there is still a strong interaction between the mineral crystal and WSF. Therefore, the mineral still grows in an oriented manner in the WSF.

[0081] In this example, after the concentration of the mineralization system was changed to 10 mM, the XRD patterns of the minerals regulated by the two proteins (the concentrations of SF and WSF proteins were 0.25 wt%, 0.01 wt%, and 0.05 wt%, and the reaction time was 0.5-2 h) were obtained. Fig. 20 ) and FTIR( Fig.21 ) The test also showed that high concentrations of silk fibroin would inhibit mineral crystallization. When the protein concentration was reduced or the mineralization reaction time was prolonged, more crystals would form in the solution. After 2 hours of mineralization, low concentrations of SF had a weak inhibitory effect on mineral crystallization, but the WSF control system still had an inhibitory effect on mineral growth, which was particularly evident in the FTIR results. The characteristic absorption peak of DCPD is at 1120 cm -1 、1053cm -1 and 984cm -1 At the position, the low concentration of 0.05wt% SF ( Fig.21 c) The minerals obtained by adjusting for 2h have stronger absorption peaks at these three locations. Fig. 20 d) The regulated minerals are still in the intermediate state of crystal phase transition, with a peak at 1116 cm -1 and 985cm -1 The absorption peak intensities at the 10 mM mineralization system protein were all weak, indicating that WSF had a stronger regulatory effect on minerals. Fig.21 ) and FTIR results of 5mM 0.05wt% protein regulated mineralization ( Fig.12 ) for comparison. Although the protein concentration in the solution was low, the generated mineral still contained -1 and 1515cm -1 In the 10 mM solution, although the concentration of the mineralized system increased and the relative content of silk fibroin decreased, in the result of 2 h of low concentration SF regulation, the absorption peak at 1525 cm -1 The characteristic absorption peak of silk fibroin at the position almost disappears, proving that the content of silk fibroin in the mineral is relatively low. As the mineral crystallization rate accelerates, the hybridization between mineral and protein decreases, resulting in a weakened regulatory effect of the protein. This result is consistent with the analysis results of the scan.

[0082] From the above detailed description of the embodiments of the present invention, it can be understood that the reaction conditions of the present invention are mild, the operation is simple, it can be carried out at room temperature, and the experimental repeatability is good. By adjusting the concentration of the water-soluble segments of silk fibroin during the experiment, the reaction time and the concentration of the mineralization system, silk fibroin-calcium phosphate with different monomer structures and assembly structures can be obtained. Specifically, the WSF solution contains more positively charged amino acids, which reduces the repulsion between negatively charged amino acids and forms a cluster structure of WSF. At the beginning of the mineralization reaction, Ca 2+ Binds to protein clusters due to the presence of Ca on the surface of protein clusters 2+ At high concentrations, minerals on the cluster surface rapidly nucleate. Crystals grow in combination with WSF clusters, and the β-folded structure inside the protein core regulates the oriented crystallization of minerals. At the same time, since WSF combines with minerals to form a coating structure, it inhibits the rate of collision crystallization of calcium / phosphorus ions in the solution. Therefore, WSF will have an inhibitory effect on the growth of minerals. In the mineralization process regulated by SF, due to the negatively charged amino acids contained in the solution, the electrostatic repulsion inside makes the amino acids evenly dispersed in the solution, and SF and mineral crystals grow hybridly, in which the complex protein regulates the morphology of the crystals. Higher protein concentrations inhibit the interaction between calcium / phosphorus ions and affect crystal growth. With the extension of mineralization time, the mineral gradually transforms to a more stable thermodynamic state, and eventually the spindle-shaped small particles will assemble to form flake DCPD. However, when the concentration of the mineralization system is increased, the interaction between the crystal and SF in the solution is reduced, and the degree of hybridization between protein and mineral is reduced. Therefore, in the process of mineral crystallization, the inhibitory and regulatory effects of protein on mineral growth are weakened. In view of the deficiencies in the prior art, the present invention provides a new method for preparing a composite material with different monomer morphologies and assembly structures by using the same material as a template.

[0083] It is to be understood that the above embodiments are merely exemplary embodiments for illustrating the principles of the present invention, and the present invention is not limited thereto. For those skilled in the art, various modifications and improvements may be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered as the protection scope of the present invention.

[0084] The upper and lower limits, interval values ​​of the raw materials of the present invention, as well as the upper and lower limits, interval values ​​of the process parameters (such as silk fibroin concentration, mineralization solution concentration and mineralization time, etc.) can realize the present invention, and the embodiments are not listed one by one here.

Claims

1. A method for preparing a silk-mineral composite material induced by synthesizing a water-soluble silk segment as a template, wherein the silk-mineral composite material is obtained by inducing the orderly growth of calcium ions and hydrogen phosphate ions by the water-soluble silk segment, and is a bulk mineral formed by a spindle-like structure of silk fibroin and amorphous calcium phosphate growing along the c-axis, or rod-shaped calcium hydrogen phosphate crystals growing in parallel, and the surface of the bulk mineral is coated with silk fibroin, characterized in that: The specific steps are as follows: 1) Preparation of water-soluble silk fibroin segment solution: soak degummed silk in lithium bromide solution and heat to dissolve to obtain a crude solution, place the crude solution in a dialysis bag, dialyze in deionized water to remove salt ions, and then centrifuge to obtain a regenerated silk fibroin solution. Spread the regenerated silk fibroin solution in a culture dish and place it in a clean bench to dry to obtain a silk fibroin membrane. Cut the obtained silk fibroin membrane into pieces and soak it in deionized water, place it on a shaker for 60-90 minutes, and centrifuge to obtain the supernatant and dilute it to obtain a WSF solution. 2) Preparation of silk-mineral composite materials induced by the water-soluble segments of silk as templates: CaCl2 was dissolved in the WSF solution obtained in step 1) to obtain a WSF solution containing CaCl2, a mixed solution of KH2PO4 and Na2HPO4 was placed in an ice-water bath for 30 min, and the pH value of the solution was stabilized at 6±0.5, and then the WSF solution containing CaCl2 was added to the mixed solution of KH2PO4 and Na2HPO4 for mineralization reaction. After the reaction, the solid product was collected by centrifugation to obtain a silk-mineral composite material induced by the water-soluble segments of silk as templates.

2. The method for preparing a silk-mineral composite material using a water-soluble silk segment as a template for induction synthesis according to claim 1, characterized in that: Step 1) The lithium bromide solution is obtained by dissolving lithium bromide in water, and the concentration is 9.3M; the mass volume ratio of the degummed silk to the lithium bromide solution is 0.15-0.25g / mL.

3. The method for preparing a silk-mineral composite material using a water-soluble silk segment as a template for induction synthesis according to claim 1, characterized in that: Step 1) The process conditions of soaking the degummed silk in a lithium bromide solution and heating and dissolving the degummed silk are: stirring at 60° C. at a rate of 200 to 400 rpm for 2 to 4 hours.

4. The method for preparing a silk-mineral composite material using water-soluble silk segments as templates for induction synthesis according to claim 1, characterized in that: Step 1) the concentration of the regenerated silk fibroin solution is 6-7wt%; Step 1) the obtained silk fibroin membrane is cut into pieces and then immersed in deionized water, and the mass volume ratio of the silk fibroin membrane to the deionized water is 0.05-0.15g / mL.

5. The method for preparing a silk-mineral composite material using water-soluble silk segments as templates for induction synthesis according to claim 1, characterized in that: Step 1) The concentration of water-soluble segments of silk fibroin in the WSF solution is 0.05-0.25 wt %.

6. The method for preparing a silk-mineral composite material using water-soluble silk segments as templates for induction synthesis according to claim 1, characterized in that: Step 2) The concentration of CaCl2 in the WSF solution containing CaCl2 is 5-10 mM; Step 2) The concentration of hydrogen phosphate in the mixed solution of KH2PO4 and Na2HPO4 is 5-10 mM, wherein the mass ratio of KH2PO4 to Na2HPO4 is 1:3.

65.

7. The method for preparing a silk-mineral composite material using water-soluble silk segments as templates for induction synthesis according to claim 1, characterized in that: Step 2) The molar ratio of calcium in the WSF solution containing CaCl2 to phosphorus in the mixed solution of KH2PO4 and Na2HPO4 is 1.67:1, and the Ca 2+ The concentration is 5~10 mM.

8. The method for preparing a silk-mineral composite material using water-soluble silk segments as templates for induction synthesis according to claim 1, characterized in that: Step 2) The mineralization reaction conditions are: react at room temperature for 0.5 to 24 hours.

Citation Information

Patent Citations

  • Fibroin-calcium hydrophosphate compound obtained through induction by taking fibroin as template and preparation method thereof

    CN111603607A

Cited By

  • Mineralized protein-based bionic bone repair material as well as preparation method and application thereof

    CN121177579A